First study of water quality in the san camilo and mojahuevo estuaries located in guayas for being used in aquaculture - Rodríguez-Grimón, René (2021)
The water quality of the San Camilo and Mojahuevo estuaries was monitored in the months of April (rainy season) and June (dry season) of 2016. The water of the Mojahuevo estury presented in both seasons the lowest values of turbidity between 17.20 and 33.70 UNT, biochemical oxygen demand being in a range between 14.00 and 19.00 mg/L, zinc content (0.02-0.05 mg/L) and copper content (0.07 mg/L), ammonia content (0.21-0.35 mg/L), fats and oils (0.23-0.29 mg/L), phosphates (0.39-2.34 mg/L) and nitrates (0.84-2.29 mg/L), while the water of the two estuaries San Camilo and Mojahuevo (rainy season) showed similar phenolic content (0.019 mg/L). The results showed that the Mojahuevo estuary presented the high quality of water recommended for being used in productive process like aquaculture due to the low presence of pollutants